2019
DOI: 10.1104/pp.19.00919
|View full text |Cite
|
Sign up to set email alerts
|

K+ Channel-SEC11 Binding Exchange Regulates SNARE Assembly for Secretory Traffic

Abstract: Cell expansion requires that ion transport and secretory membrane traffic operate in concert. Evidence from Arabidopsis (Arabidopsis thaliana) indicates that such coordination is mediated by physical interactions between subsets of so-called SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins, which drive the final stages of vesicle fusion, and K 1 channels, which facilitate uptake of the cation to maintain cell turgor pressure as the cell expands. However, the sequence of SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
(176 reference statements)
0
17
0
Order By: Relevance
“…The exocyst forms a peripheral membrane complex (Fendrych et al, 2013;Synek et al, 2014;Kulich et al, 2018). The Qa-and R-SNAREs are integral membrane proteins; whereas SYP121 localizes to the plasma membrane (Lipka et al, 2007;Honsbein et al, 2009;Grefen et al, 2015;Waghmare et al, 2019), the R-SNAREs, including VAMP721, localize to the vesicle membrane and associate transiently with the plasma membrane (Uemura et al, 2005;Zhang et al, 2011Zhang et al, , 2015. We therefore asked whether the loss of one interacting partner could affect the localization of the other as a possible mechanism to explain secretory block.…”
Section: Snare Protein Localization Is Altered In the Exo70a1 Mutantmentioning
confidence: 99%
“…The exocyst forms a peripheral membrane complex (Fendrych et al, 2013;Synek et al, 2014;Kulich et al, 2018). The Qa-and R-SNAREs are integral membrane proteins; whereas SYP121 localizes to the plasma membrane (Lipka et al, 2007;Honsbein et al, 2009;Grefen et al, 2015;Waghmare et al, 2019), the R-SNAREs, including VAMP721, localize to the vesicle membrane and associate transiently with the plasma membrane (Uemura et al, 2005;Zhang et al, 2011Zhang et al, , 2015. We therefore asked whether the loss of one interacting partner could affect the localization of the other as a possible mechanism to explain secretory block.…”
Section: Snare Protein Localization Is Altered In the Exo70a1 Mutantmentioning
confidence: 99%
“…In addition, Zhang and colleagues discovered that the R-SNARE AtVAMP721 also interacts with KAT1 but also with another K + -channel, KC1, indicating a tight regulation between the K + -channels and the AtSYP121/AtVAMP721 SNARE complex (Zhang et al, 2015(Zhang et al, , 2017. Finally, Waghmare et al (2019) determined that the Qb,c-SNARE AtSNAP33 stabilises the AtSYP121/AtVAMP721 SNARE complex after priming of the Qa-SNARE AtSYP121 through its interaction with K + -channel. It was suggested that this binding could correspond to a primary state for initiating the secretory/fusion machinery for exocytosis.…”
Section: Snares In Ion Transport Regulationmentioning
confidence: 99%
“…Finally, Waghmare et al . (2019) determined that the Qb,c‐SNARE AtSNAP33 stabilises the AtSYP121/AtVAMP721 SNARE complex after priming of the Qa‐SNARE AtSYP121 through its interaction with K + ‐channel. It was suggested that this binding could correspond to a primary state for initiating the secretory/fusion machinery for exocytosis.…”
Section: Snares In the Secretory Pathwaymentioning
confidence: 99%
“…We now know that, along with SYP121, the Qbc-SNARE SNAP33 and the R-SNARE VAMP721 bind to the channel VSD domain through a conserved RYxxWE motif located at the N-terminal cytosolic end of the channel and close to the S1 α-helix ( Figure 5 ; Grefen et al, 2015 ; Zhang et al, 2015 ; Waghmare et al, 2019 ). Additionally, the channel binds with the regulatory protein SEC11, a member of the SEC1/MUNC18 protein family that regulates SNARE assembly and secretory traffic ( Karnik et al, 2013 , 2015 ; Waghmare et al, 2019 ).…”
Section: Kv Channel Gating Regulation By Ancillary Proteinsmentioning
confidence: 99%